Respiratory syncytial virus prevalence in children admitted to five Kenyan district hospitals: a cross-sectional study - Mark Lee; Jacqueline Le Geyt; Stephanie Hauck; Jennifer Mackintosh; Jessica Slater; Duke Razon; Bhanu Williams (BMJ Publishing Group, 2019)
Acute respiratory infections (ARIs) are a leading cause of under-five mortality globally. In Kenya, the reported prevalence of respiratory syncytial virus (RSV) infections in single-centre studies has varied widely. Our study sought to determine the prevalence of RSV infection in children admitted with ARI fulfilling the WHO criteria for bronchiolitis. This was a prospective cross-sectional prevalence study in five hospitals across central and highland Kenya from April to June 2015. Two hundred and thirty-four participants were enrolled. The overall RSV positive rate was 8.1%, which is lower than in previous Kenyan studies. RSV-positive cases were on average 5 months younger than RSV-negative cases.